Analisis Kinerja Keuangan Daerah Kabupaten Ciamis - Rusliana, Nanang; Rustandi, Andi; Lestari Komarlina, Dwi Hastuti (WELFARE Jurnal Ilmu Ekonomi, 2020)
The purpose of this study is to assess the regional financial independence in financing the implementation of regional autonomy, measure the effectiveness and efficiency in realizing regional revenue, measure the extent to which regional government activities spend their regional revenue, measure the contribution of each source of income in the formation of regional revenue, and see the growth/ the development of revenue and expenditure earned during a certain period. The method used in this research is descriptive method of the budget and regional financial achievements or realization. The method used in this research is descriptive method of the budget and regional financial achievements or realization. The analytical tools used in this study use the Regional Financial Independence Ratio Analysis (RKKD) and the Analysis Effectiveness Ratio and Efficiency Ratio. The conclusions of this study are (1) The financial independence of Ciamis District from 2013 to 2018 is still low by showing a pattern of instructive relationships, where the role of the central government is more dominant in terms of assistance in the form of the General Allocation Fund (DAU). (2) In the 2013 until the observation in 2018 it turns out that the ability of the financial effectiveness level of the Ciamis District based on the effectiveness ratio has been effective in realizing the achievement of regional income against the revenue budget that has been prepared/ planned. On the other hand, for the ratio of effectiveness of regional spending, that Ciamis District is still categorized as inefficient in its ability to spend regional finances. Tujuan penelitian ini adalah untuk menilai kemandirian keuangan daerah dalam membiayai  penyelenggaraan otonomi daerah, mengukur efektivitas dan efisiensi dalam merealisasikan pendapatan daerah, mengukur   sejauhmana   aktivitas   pemerintah   daerah   dalam  membelanjakan pendapatan daerahnya, mengukur kontribusi masing-masing sumber pendapatan dalam pembentukan pendapatan daerah, dan melihat pertumbuhan/perkembangan perolehan pendapatan dan pengeluaran yang dilakukan selama periode tertentu. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dari anggaran beserta capaian atau realisasi keuangan daerah. Alat analisis yang digunakan dalam penelitian ini menggunakan Analisis Rasio Kemandirian Keuangan Daerah (RKKD) serta Analisis Rasio Efektivitas dan Rasio Efisiensi. Kesimpulan dari penelitian ini adalah (1) Kemandirian keuangan Kabupaten Ciamis dari tahun 2013 sampai 2018 tergolong masih rendah dengan menunjukkan pola hubungan instruktif, dimana peranan pemerintah pusat lebih dominan dalam hal bantuan dalam bentuk Dana Alokasi Umum (DAU). (2) Pada pengamatan tahun 2013 sampai dengan tahun 2018 ternyata kemampuan tingkat efektivitas keuangan daerah Kabupaten Ciamis berdasarkan rasio efektivitas sudah efektif dalam merealisasikan capaian pendapatan daerah terhadap anggaran pendapatan yang telah disusun/direncanakannya. Di sisi lain untuk rasio efektivitas belanja daerah, dinyatakan bahwa Kabupaten Ciamis terkategori kurang efisien dalam kemampuan membelanjakan keuangan daerahnya.